Granulasi dengan Matrix dari Residu Ekstraksi Kunyit sebagai Upaya Produksi Pakan Ayam Pedaging - Yeni Farida; Heru Sasongko; . Sugiyarto; Agung Budihardjo (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Feed is an important aspect of the farm. Feeding not only consider nutritional factors but also economic factors. The evidence suggests that drugs such as antibiotics are added to feed for fattening purposes. Utilization of natural materials have a minimal risk of side effects. Turmeric (Curcuma domestica) is the most dominant medicinal plant that produces a lot of waste extraction. This activity aimed to reprocessing of residual extraction becomes an added value commodity such as feed. Patner of this programe was UKOT Naturafit Thibbunnabawi. The feed that produced meets the standar of feed for broilers. Counseling and training can improve participants' knowledge about the use of traditional medicine residues to modify animal feed and motivate participants to develop a farm business.